Sit Less and Move More—A Multicomponent Intervention With and Without Height-Adjustable Workstations in Contact Center Call Agents: A Pilot Randomized Controlled Trial. Issue 1 (January 2021) - Morris, Abigail S.; Murphy, Rebecca C.; Hopkins, Nicola D.; Low, David A.; Healy, Genevieve N.; Edwardson, Charlotte L.; Collins, Brendan; Timpson, Hannah; Shepherd, Sam O.; Cochrane, Madeleine; Gavin, David; Graves, Lee E.F.
Abstract : Objective: To pilot a multicomponent intervention to sit less and move more, with (SLAMM+) and without (SLAMM) height-adjustable workstations, in contact center call agents. Methods: Agents were individually randomized to SLAMM or SLAMM+ in this 10-month, parallel, open-label, pilot trial. Mixed-methods assessed response, recruitment, retention, attrition and completion rates, adverse effects, trial feasibility and acceptability, preliminary effectiveness on worktime sitting, and described secondary outcomes. Results: The participant recruitment rate, and randomization, data collection, and interventions were mostly acceptable. Refinements to organization recruitment were identified. High staff turnover negatively impacted retention and completion rates. The multicomponent intervention with height-adjustable workstations has potential to reduce sitting time at work. Conclusions: The demonstrated findings will help prepare for a future randomized controlled trial designed to assess the effect of the interventions. Abstract : Supplemental Digital Content is available in the text